Views of health care professionals on the implementation of preoperative advance care planning in older patients with head and neck cancer: Q methodology - Huixian Yang; Ruirui Duan; Yongxia Ding; Jing Xu; Yanzhi Tian (Elsevier, 2024)
Objective: To investigate the views of health care professionals in a head and neck surgical department toward the implementation of advance care planning prior to surgery for older patients with head and neck cancer. Method: Q methodology was used to explore and analyze participants' views by combining quantitative and qualitative methods. Participants were asked to rank 35 Q statements generated via semi-structured interviews and a literature review and to explain the reasons for their ranking in subsequent interviews. The data was then analyzed and used to develop a factor series to illustrate participants' views. Results: This study surveyed 15 health care professionals, including eight doctors and seven nurses. The views of health care professionals toward preoperative implementation of advance care planning discussions were varied and could be categorized into three types: defending the autonomy of patients, patients' knowledge and the Chinese traditional cultural context hinder the implementation of preoperative advance care planning, and lack of confidence in performing preoperative advance care planning. Conclusions: Although the health care professionals in the head and neck surgical department in this study recognized the benefits of preoperative discussions regarding advance care planning, patients' knowledge level, traditional Chinese values, inadequate capacity among health care professionals, and unsound legal policies have caused these professionals to have misgivings about preoperative counseling and discussing advance care planning with patients. Further studies should be conducted, and strategies to overcome barriers to discussions of preoperative advance care planning should be developed.